DISEMINASI PAKET TEKNOLOGI DALAM PENINGKATAN PRODUKSI JAGUNG PULUT - Ralle, Andi; Edy, Edy; Husain, Tsalis Kurniawan (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2022)
The goal to be achieved in this Service Program is to form a Kelompok Tani Campagaya in Campagaya Village, Galesong District, Takalar Regency to be independent in the management of out-grown maize through effective cultivation techniques in producing seeds, increasing seed production for food and an effective and efficient waxy corn marketing system. The problem with Partner farmer group is the low yield of waxy corn production due to seed and maintenance factors. The program will be conducted in December 2021 using the active participation method. The Kelompok Tani Campagaya is involved and active in participating in counseling about the cultivation of big maize, training on the make of fertilizers and pesticides and how to apply them, providing knowledge about marketing strategies for results through collaboration between farmer groups and traders and supermarkets and online systems. The results obtained in this service program are the potential for increased production of waxy corn, experience in making organic fertilizer products and natural pesticides, and being able to apply them to their crops, as well as understanding management and marketing strategies for waxy corn